2015
DOI: 10.1016/j.yexmp.2015.07.010
|View full text |Cite
|
Sign up to set email alerts
|

IL-9 signaling affects central nervous system resident cells during inflammatory stimuli

Abstract: Interleukin (IL) 9, a dominant cytokine in Th9 cells, has been proven to play a pathogenic role in experimental autoimmune encephalomyelitis (EAE), an animal model of multiple sclerosis (MS), by augmenting T cell activation and differentiation; however, whether IL-9 signaling affects central nervous system (CNS)-resident cells during CNS autoimmunity remains unknown. In the present study, we found that the IL-9 receptor (IL-9R) was highly expressed in astrocytes, oligodendrocyte progenitor cells (OPCs), oligod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
27
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(34 citation statements)
references
References 25 publications
7
27
0
Order By: Relevance
“…Previous studies have shown that in vitro-cultured astrocytes express IL-9R (12). This study verified those results and showed, for the first time to our knowledge, that the astrocyte markers GFAP and IL-9R were colocalized in the brains of rats.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Previous studies have shown that in vitro-cultured astrocytes express IL-9R (12). This study verified those results and showed, for the first time to our knowledge, that the astrocyte markers GFAP and IL-9R were colocalized in the brains of rats.…”
Section: Discussionsupporting
confidence: 91%
“…Our preliminary data demonstrate that IL-9 is highly expressed in peripheral blood mononuclear cells from patients with IS and that IL-9 can aggravate the destruction of the BBB by acting on endothelial cells in the OGD model (11). Additionally, previous studies have suggested that the IL-9 receptor (IL-9R) is highly expressed in astrocytes (12). However, the effect of IL-9 on astrocytes during ischemic brain injury has not been explored.…”
mentioning
confidence: 86%
“…Another recent study showed that IL‐9 negatively regulates Th17 cells . In addition, IL‐9 levels in the CSF of MS patients were shown to negatively correlate with inflammation, neurodegeneration, and disease progression , supporting a regulatory role for IL‐9 in MS. An in vitro study showed that IL‐9 in the presence of IFN‐γ promotes the proliferation of oligodendrocyte precursor cells, whereas IL‐9 in the presence of IL‐17 inhibits oligodendrocyte precursor cell proliferation, suggesting that Th9 cells may have inverse functions in the presence of Th1 or Th17 cells .…”
Section: Introductionmentioning
confidence: 99%
“…TNFα, IL2, and IL6 are another set of dysregulated cytokines that play crucial role in synaptic plasticity, homeostatic control, glutamate mediated cytotoxicity, potentiation, sleep, and communication between the immune and endocrine systems [62,64,75]. Further analysis of TNFα is crucial because this cytokine holds a central position in relation to a plethora of CNS conditions, including CNS-TB, autism and multiple sclerosis [64,76,77]. MS patients also demonstrate up-regulation in many of these cytokines in their CSF and serum, all of which are found to be up-regulated upon treatment with BafA1 and some with Rapa (Table 3) [73].…”
Section: Implications Of Bafa1/rapa-dysregulated Secreted Cytokinesmentioning
confidence: 99%
“…IL9 receptors are present on astrocytes, oligodendrocytes and microglia, and IL9 dysregulation has been reported in CNS pathologies such as autoimmune encephalitis, oligodendrocyte progenitor cell proliferation and differentiation. Thus, such drug treatment that may mimic these CNS pathologies in patients being administered these drugs, warrants extreme caution and further investigation [77].…”
Section: Implications Of Bafa1/rapa-dysregulated Secreted Cytokinesmentioning
confidence: 99%